Exploring the Utility of Self-Control Theory for Risky Behavior and Minor Delinquency Among Chinese Adolescents. (February 2013) - Lu, Yi-Fen; Yu, Yi-Chun; Ren, Ling; Marshall, Ineke Haen
Although scholarly interest in empirically assessing Gottfredson and Hirschi's (1990) self-control theory continues to grow, there is little research available on evaluating its utility in China. The current study examines the power of self-control theory as an explanation of juvenile minor risky behavior as well as minor delinquent behaviors in China, while simultaneously considering the role of social bonds. The data were collected from a probability sample of 7th, 8th, and 9th graders in Hangzhou, China ( N = 1, 043) using the second International Self-Report Delinquency (ISRD-2) survey instrument. The results from the logistic regression analyses show that self-control is associated with both measures of Chinese youth deviance in the expected direction, suggesting that the youth with low self-control have a higher likelihood to report minor risky and delinquent behavior. The effects of self-control remain when controlling for social bonding measures. Among the social bonding factors, beliefs (pro-violence attitude) and family bonding were found to be the significant predictors of risky behavior and minor delinquency, respectively.